Abnormal Achilles tendon US findings in Mexican patients with type 2 diabetes - Ivan Martinez-Flores; David Aguilar-Obeso (Journal of the Mexican Federation of Radiology and Imaging)
Introduction. Achilles tendon abnormalities on ultrasound (US) have been associated with type 2 diabetes. This study aimed to identify the Achilles tendon US findings in Mexican patients with type 2 diabetes. Material and methods: This was a cross-sectional study of adult patients with type 2 diabetes. The variables recorded were age, sex, time since diagnosis of type 2 diabetes, body mass index (BMI), glycosylated hemoglobin, and treatment. Both Achilles tendons were examined with US and the abnormal findings were fibrillar disorganization, intrasubstance calcifications, hypoechoic foci, and increased Achilles tendon thickness. Results: Seventy Achilles tendons were examined in 35 type 2 diabetes patients. The mean age was 55.7 ± 12.02 years. Twenty-nine (82.8%) were women, and 6 (17.2%) were men. US abnormalities were found in 60 Achilles tendons in 33 (94.3%) of 35 patients. Intrasubstance calcifications were the most common finding in both tendons (n = 29, 50.8% right and n = 24, 47.1% left), followed by fibrillar disorganization (n = 14, 24.6% right and n = 17, 33.3% left). Thickening was found in only two (3.5%) right tendons. Overweight or obese patients had more abnormal US findings in the Achilles tendon. Conclusion: Abnormal US findings of the Achilles tendon were prevalent in patients with type 2 diabetes. The most common were intrasubstance calcifications, followed by fibrillar disorganization.